(untitled) (Research, Society and Development, 2022)
The Brazilian psychiatric reform represents an attempt to change the paradigm of mental health care. To analyze what scientific productions and official documents are about the impacts of the new mental health policy for the psychosocial care of people with mental suffering. Studies found in the following databases: Latin American and Caribbean Literature on Health Sciences (LILACS), Publisher Medline (PUBMED) and Scientific Electronic Library Online (Scielo) were analyzed. been most studies were published in the last five years. The trajectory of mental health in Brazil is marked by different models of care. Changes in epistemological and symbolic conceptions about mental illness, as well as the socio-political and economic contexts and the forms of organization of the health system, contributed to the transformation of approaches and institutions. Thus, the Mental Health Policy was highlighted, with emphasis on Ordinance 336/2002, which reorganized mental health care in Brazil with the definition of Psychosocial Care Centers. humanized and multiprofessional, with the possibility of reintegrating the individual into society without the use of asylum and hospitalization services. The discussion of the results found reinforced the impact of the setback in the field of mental health with the implementation of measures that encourage the return of the hospital-centered, excluding and medicalizing model.